2016
DOI: 10.1038/srep24082
|View full text |Cite
|
Sign up to set email alerts
|

A common theme in extracellular fluids of beetles: extracellular superoxide dismutases crucial for balancing ROS in response to microbial challenge

Abstract: Extracellular Cu/Zn superoxide dismutases (SODs) are critical for balancing the level of reactive oxygen species in the extracellular matrix of eukaryotes. In the present study we have detected constitutive SOD activity in the haemolymph and defensive secretions of different leaf beetle species. Exemplarily, we have chosen the mustard leaf beetle, Phaedon cochleariae, as representative model organism to investigate the role of extracellular SODs in antimicrobial defence. Qualitative and quantitative proteome a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 98 publications
(105 reference statements)
3
12
0
Order By: Relevance
“…Among them, Cu/Zn-SOD2 showed the highest fold expression in winged imagoes against the most pathogenic isolate M. anisopliae 02049. The high upregulation is in agreement with other studies on the first-line insect antioxidant defense genes against fungal infection [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Among them, Cu/Zn-SOD2 showed the highest fold expression in winged imagoes against the most pathogenic isolate M. anisopliae 02049. The high upregulation is in agreement with other studies on the first-line insect antioxidant defense genes against fungal infection [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Results showed significant differences in the SOD activities of date-palm dust mites calculated at different times (F = 48.55; df = 12, 24; P < 0.0001), with different fungal isolates (F = 85.27; df = 2, 24; P < 0.0001), and their interaction (F = 356.29; df = 4, 24; P < 0.0001) as shown in Table 2. The highest SOD activity, as depicted in the present results, among datepalm dust mites at the start of infection agrees with the results of Gretscher et al (2016) and Hussain et al (2017). However, a decline in SOD activities with time from the most virulent isolate 2049, corroborates with AlJabr et al (2018), who suggested that decline in SOD activities at a lateral infection stage from virulent isolates led to ROS elimination failure.…”
Section: Evaluation Of Oligonychus Afrasiaticus Antioxidant Defense Msupporting
confidence: 92%
“…A second hypothesis arises from the intriguing finding in our phylogenetic analysis, revealing that the two variants of tc-sodb are most closely related to the SOD3 isoforms of the mustard leaf beetle P. cochlearis . Interestingly, in this coleopteran species, substantial EC-SOD activity is found in the haemolymph as well as in the defensive secretions, and SOD-deficient larvae showed increased mortality when challenged with the entomopathogenic fungus Metarhizium anisopliae ( 59 ). Defensive secretions also play an important role in T. castaneum for the regulation of the flour microbiota ( 60 , 61 ), but a potential role of SOD in these fluids needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%